The Hypotensive Role of Acupuncture in Hypertension: Clinical Study and Mechanistic Study - Fan, Hao; Yang, Jing-Wen; Wang, Li-Qiong; Huang, Jin; Lin, Lu-Lu; Wang, Yu; Zhang, Na; Liu, Cun-Zhi (Frontiers in Aging Neuroscience, 2020)
As a component of traditional Chinese medicine, acupuncture has the potential to lower blood pressure (BP) in patients with hypertension. Emerging evidence indicates that the acupuncture-induced inhibition of high BP occurs through the activation of the pathway in the afferent, central and efferent pathways. An increasing number of studies have demonstrated that acupuncture not only activates distinct brain regions under conditions of hypertension caused by an imbalance between the sympathetic and parasympathetic systems but also modulates neurotransmitters in related brain regions to alleviate the autonomic response. The activity of these pathways can be assessed by injecting agonists or inhibitors or by performing neurotomy. This review focuses on the clinical and mechanistic studies of acupuncture in modulating BP, which might provide a neurobiological foundation for the effects of acupuncture. Although many mechanisms underlying the effects of acupuncture on cardiovascular function have been identified, further investigation is clearly warranted.